2022
DOI: 10.1016/j.ultsonch.2021.105860
|View full text |Cite
|
Sign up to set email alerts
|

Does salting-out effect nucleate nanobubbles in water: Spontaneous nucleation?

Abstract: Highlights Nanobubble density during salting-out effect increases with salting-out parameter. An ultrasound field with a high amplitude destroys the nanobubbles in salt solution. R.I. of nanobubbles in NaCl and AlCl 3 were estimated to be 1.012 and 1.302, respectively. The NBs during salting-out effect are observed to be stable only for up to three days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…The SBR process had also a high ability to remove nitrogen because of the occurring nitrification process. As a final deduction about all the mentioned results, it was confirmed that the NB aeration system could give considerably promoted efficiencies in all terms of the tested treatment effective parameters (Agarwal et al, 2022a;Agarwal et al, 2022b;Harsh Sharma and Nirmalkar, 2022;Li and Zhang, 2022).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The SBR process had also a high ability to remove nitrogen because of the occurring nitrification process. As a final deduction about all the mentioned results, it was confirmed that the NB aeration system could give considerably promoted efficiencies in all terms of the tested treatment effective parameters (Agarwal et al, 2022a;Agarwal et al, 2022b;Harsh Sharma and Nirmalkar, 2022;Li and Zhang, 2022).…”
Section: Discussionmentioning
confidence: 54%
“…However, there is a lack of information about the comparison of the removal efficiency of pollutants in wastewater treatment systems using FB and NB aeration (Agarwal et al, 2022a;Agarwal et al, 2022b;Harsh Sharma and Nirmalkar, 2022;Li and Zhang, 2022). Hence, this research work aimed to experimentally compare the efficiency of FB and NB aeration in treating wastewater through the SBR system.…”
Section: Introductionmentioning
confidence: 99%
“…NTA (nanoparticle tracking analysis) and DLS (dynamic light scattering) were used to characterize the nanobubble sample under atmospheric conditions . The results were presented in terms of the bubble size distribution, concentration of nanobubbles, bubble diameters, and zeta potential.…”
Section: Materials and Methodologiesmentioning
confidence: 99%
“…NTA (nanoparticle tracking analysis) and DLS (dynamic light scattering) were used to characterize the nanobubble sample under atmospheric conditions. 38 The results were presented in terms of the bubble size distribution, concentration of nanobubbles, bubble diameters, and zeta potential. The concentration of nanobubbles increases monotonically with time, and the mean diameter lies in the range of 100−120 nm as shown in Figure 2b.…”
Section: Nanobubble Generationmentioning
confidence: 99%
“…The refractive index of NBs was taken as 1. 58 For each experimental condition, several samples of NBs were prepared at different dilution factors and ζ were measured. The primary rationale for diluting the NBs concentrations was a relatively high NBs concentration per 1 mL of solution.…”
Section: ζ-Potential Measurement the Electrical Potential Of Bubbles ...mentioning
confidence: 99%